Pelaksanaan Perjanjian di Bawah Tangan Antara Datasemen Kesehatan Wilayah Kupang dengan CV. Citra - Dewi Rahayu S. Gah; Yossie M.Y. Jacob; Helsina F. Pello (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
In the employment agreement held by CV. Citra with the Kupang Regional Health Detachment is a type of private agreement. Thus, as long as the parties carry out a legal act to make a private agreement, the agreement has binding legal force like a law for the parties who make it. CV. Citra and the Kupang Regional Health Detachment have a work cooperation agreement. In the Agreement, CV. Citra has an obligation to fulfill health services at the Kupang Regional Health Detachment in the form of providing pharmacy facilities through a recommendation application for renting State Property (BMN) in the form of land/land to be utilized. This study aims to determine and analyze the strength and legal impacts that occur in the employment agreement between CV Citra and the Kupang Regional Health Detachment. This study is an empirical legal research, where the research is called qualitative research, namely research that produces descriptive-analytical data. The results of the study indicate that the binding power of an underhand agreement between CV. Citra with the Kupang Regional Health Detachment based on the discussion above already has a binding force between the two parties who entered into a cooperation agreement with Number: PKS / 01 / IX / 2008, dated September 11, 2008 which has been registered / Warmeking legalized by Notary Silvester Joseph Mambaifeto, S.H, under Number; 206 / 2018, dated September 11, 2008. The legal impact if one party defaults on an agreement in this case the case between CV. Citra Kartika and the Kupang Regional Health Detachment based on the discussion above after holding various meetings to find a consensus but not finding a consensus, CV. Citra Kartika demands material and immaterial compensation from the Kupang Regional Health Detachment in the amount of Rp. 10,354,700,000,000.